1973
DOI: 10.1029/ja078i001p00171
|View full text |Cite
|
Sign up to set email alerts
|

A semiempirical model of large-scale magnetospheric electric fields

Abstract: Semiempirical analytic formulas for large‐scale electric magnetospheric fields are developed that are valid within the inner magnetosphere as well as within the ionosphere. These electric fields drive ionospheric electric currents. Moreover, field‐aligned electric currents must exist in order to maintain the magnetospheric electric field configuration. The model calculations are compared and are shown to be consistent with the shape of the plasmapause, the equivalent electric current systems of DP 1 and DP 2, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
416
0
1

Year Published

1998
1998
2014
2014

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 486 publications
(427 citation statements)
references
References 27 publications
10
416
0
1
Order By: Relevance
“…They interpreted this auroral boundary as the earthward boundary of the plasma sheet and showed that its variations are empirically well described by the Volland-Stern electric field model [Volland, 1975;Stern, 1975]. Best fits were obtained with the Volland-Stern parameter 9' •-' 2.…”
Section: Introductionmentioning
confidence: 87%
“…They interpreted this auroral boundary as the earthward boundary of the plasma sheet and showed that its variations are empirically well described by the Volland-Stern electric field model [Volland, 1975;Stern, 1975]. Best fits were obtained with the Volland-Stern parameter 9' •-' 2.…”
Section: Introductionmentioning
confidence: 87%
“…In addition, y 0 is an electric potential indicating the dawn-dusk convection electric fields [Volland, 1973;Stern, 1975], which is always described as an empirical K p -dependent function [Maynard and Chen, 1975]:…”
Section: Discussionmentioning
confidence: 99%
“…All boundaries are calculated by using the dipole magnetic field model and superposition of shielded dawn-dusk electric field with a corotation electric field, which is often called the Volland-Stern electric field model [Volland, 1973;Stern, 1975]:…”
Section: Instruments and Data Analysismentioning
confidence: 99%